Chronic pain and health-related quality of life in Croatian war veterans - Braš, Marijana (Array, 2008)
Persistent pain in the musculoskeletal system is recognized as one of the most frequent physical complaints in patients with chronic post-traumatic stress disorder (PTSD). However, so far only few data exist reflecting the quality of life (QoL) in patients with chronic PTSD and chronic pain. In this study the authors analyzed the interrelationships between chronic pain, chronic PTSD and quality of life in Croatian war veterans. The 136 veterans who were treated at the Clinic for Psychological Medicine in University Hospital Centre Zagreb during year 2007 were selected as the sample for this study. On the base of medical records, interviews and different self reported questionnaires (Mississippi Scale for combat-related PTSD, Impact of Event Scale, Mc Gill Pain Questionnaire, Pain Outcomes Questionnaire-VA (POQ-VA), Brief Pain Inventory, Beck Depression Inventory, Quality Of Life Questionnaire) the authors analyzed the interrelationships between chronic pain, quality of life and chronic PTSD, as well as different therapeutical approaches that were used in the treatment. In our sample, 90 patients had severe symptoms of chronic PTSD. All patients suffered from different chronic pain syndromes. Patients with chronic PTSD had significantly higher total pain scores as well as affective and sensory pain components compared to the patients without PTSD. QoL in patients with chronic PTSD and chronic pain is significantly negatively correlated with sensory (r=-0.385 ; p<0.01) and affective component of pain (r=-0.285 ; p<0.01) as well as with total pain scores (r=-0.376 ; p<0.01). Affective component of pain were significantly correlated with the level of PTSD symptoms. Intrusive symptoms of PTSD were significantly related to pain intensity and pain disability. Interrelationship between chronic pain, chronic PTSD and quality of life requires a multidisciplinary approach to the assessment and treatment of patients with the emphasis on rational polipharmacy and psychotherapeutical interventions.